The Effect of the Numbered Heads Together (NHT) Cooperative Learning Model on the Learning Outcomes of Phase F Fashion Design Students at SMKN 6 Padang - Feni Lusiana Taileleu; Khurnia Budi Utami; Teni Suriani (The Future of Education Journal, 2026)
This study examines the effect of the Numbered Head Together (NHT) cooperative learning model on the mathematics learning outcomes of Phase F Fashion Design students at SMKN 6 Padang, addressing persistently low achievement under conventional, teacher-centered instruction. A true experimental method with a posttest-only control design was employed, involving 30 students in an experimental class taught using the NHT model and 30 students in a control class taught conventionally; the classes were selected through cluster random sampling after the population was confirmed normally distributed and homogeneous in variance. Data were collected using an essay-based achievement test that had been validated and tested for reliability. Results showed the experimental class achieved a higher mean score (80.70) than the control class (75.40), with mastery percentages of 70% and 52% against the minimum mastery criterion of 75, respectively. Since the Liliefors normality test indicated the achievement data in both groups were not normally distributed, hypothesis testing was conducted using the nonparametric Mann-Whitney U test, yielding a Zcalculated value of 2.33, which exceeded the Ztable value of 1.65 at a significance level of α = 0.05, leading to the rejection of H0 and acceptance of H1. These findings demonstrate that the NHT cooperative learning model produced significantly better mathematics learning outcomes than conventional learning among Phase F Fashion Design students. The study concludes that NHT, through its numbering and random-calling mechanism, fosters individual accountability and group cooperation, making it a viable strategy for improving student engagement and mathematics achievement in vocational secondary education.